UTILITARIAN VALUES AND HEDONIC VALUES OF WOMEN COFFEE LOVERS - Hamdan Hamdan; Paijan Paijan (Dinasti Publisher, 2020)
This study on the utilitarian values and hedonic values for women coffee lovers, aims to analyze the role of product attributes to the utilitarian values and hedonic values in shaping positive attitudes and behavior of consumers in deciding the purchase intentions. The design of this study uses descriptive-quantitative research. While the determination of the sample is women’s in West Jakarta who have consumed coffee today by using purposive sampling techniques to 148 women. The results of primary data collection will be analyzed using the SEM-Covariance method. The findings of this study indicate that product attributes have a positive and significant effect on utilitarian values and hedonic values. The utilitarian values and hedonic values have a positive significant effect on repurchase intention.